Impact of MSPO certification on profit among palm oil growers in Malaysia - Sharifuddin, Juwaidah; Lim, Fabian Chin Wen; Sinden, Ann (ISP Management (M) Sdn. Bhd., 2023)
Malaysian Sustainable Palm Oil (MSPO) certification is a regulatory requirement for all oil palm growers and processing facilities in Malaysia. However, unlike the Roundtable on Sustainable Palm Oil (RSPO), MSPO does not offer any monetary benefits. Growers have concerns about the increased costs of implementing MSPO. The objective of this research was to identify whether there was a cost increase in terms of overall cost per tonne of oil palm bunch, cost per area, and any changes in production. Similar methods to those used in numerous articles on RSPO were employed, utilising the Population, Intervention, Comparison, and Outcome (PICO) Framework coupled with a questionnaire to collect data. The data were then analysed using a paired t-test. Samples were collected from MSPO-certified estates with the assistance of the Incorporated Society of Planters (ISP) and Malaysian Estate Owners’ Association (MEOA) network. While we initially aimed to collect 72 samples, we managed to obtain 76 respondents. The findings revealed a significant cost increase per tonne of oil palm bunch, as well as an increase in cost per area after the estates adopted MSPO. However, there was also a significant recorded increase in yield production. When compared to current data, the yield increase, coupled with the oil palm price from the previous year, could not justify the increase in cost and resulted in lower profits. It would be ideal for MSPO-certified estates to obtain RSPO certification to increase their revenue, as RSPO has an impact on the selling price of the oil palm. It is recommended that future studies include an in-depth analysis to gain a more holistic and detailed understanding of the impact of sustainability certification on oil palm plantations. Furthermore, a separate study focusing solely on smallholders would be beneficial as it may reveal a different picture.